What makes terrorism salient?: Terrorist strategies, political competition, and public opinion - Criado, Henar (Terrorism and political violence, 2017)
This article analyzes the determinants of terrorism saliency in public opinion. It is usually assumed that after a terrorist attack, terrorism becomes automatically salient. However, this assumption is only true in those countries where terrorist attacks are exceptional events. In democracies that have suffered domestic terrorism for decades, the evolution of terrorism saliency does not only depend on the frequency or intensity of terrorist attacks. In this article it is claimed that the tactics carried out by terrorist groups (the type of victim, especially) and the dynamics of political competition (especially the ideology of the incumbent) are also factors that explain the evolution of terrorism saliency. The article also analyzes how these two factors interact with citizens’ predispositions to explain variation in their reactions to terrorist threat. The empirical test relies on a novel database from monthly public opinion surveys in Spain from 1993 to 2012.